Analysis of Aspects Affecting Tax Avoidance with Leverage, Sales Growth, and Corporate Risk Parameters - Khoirul Nissa; Retno Indah Hernawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Tax avoidance is a corporate strategy to reduce tax minimizing tax liabilities while remaining compliant with applicable tax regulations. This strategy is considered significant in financial management practices, as it serves as a legitimate and efficient tax planning tool to optimize a company's financial condition. The purpose of this study is to analyze the effect of leverage, sales growth, and corporate risk on tax avoidance practices in energy companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. This research employs a quantitative method utilizing secondary data gathered from annual reports of companies, which were accessed via the official website www.idx.co.id and each energy sector company's official website. The analytical method employed in this study is multiple linear regression. The population consists of energy sector firms listed on the IDX during the 2020–2024 period, and a sample of 80 data obtained using purposive sampling based on certain relevant criteria. The results of the study indicate that leverage affects tax avoidance, while sales growth and corporate risk do not affect tax avoidance. Simultaneously, leverage, sales growth, and corporate risk affect tax avoidance.